Feasibility of a Study on Gut Integrity, Microbial Translocation, Immune Activation and Vitamin D in People Living with HIV (PLWH) Who Use Illegal Drugs (P13-020-19). (13th June 2019) - Hernandez, Jacqueline; Campa, Adriana; Huffman, Fatma; Martinez, Sabrina; George, Florence; Seminario, Leslie; Jasmin, Juphshy; Baum, Marianna
Abstract: Objectives: The purpose of this study was to assess the feasibility of using the Miami Adult Studies on HIV (MASH) cohort to conduct research on markers of gut integrity, MT, immune-activation and inflammation and their relationship to Vitamin D status in this cohort. We hypothesize that drug users infected with HIV, who have vitamin D deficiency or insufficiency, will have higher levels of MT, immune-activation, inflammation and deterioration of the gut integrity than drug users infected with HIV with sufficient Vitamin D levels. Methods: Ninety HIV-infected drug users and HIV-infected drug non-users were identified from the MASH cohort with IRB approval. Data for this study will be collected at baseline, 6-months and 12-months. Laboratory analyses will include: determination of Lipopolysaccharide for MT, Soluble CD14, Interleukin 6, and Tumor Necrosis Factor alpha to assess immune-activation and inflammation; 25(OH)D levels for Vitamin D status, and Intestinal Fatty Acid Binding Protein as a gut integrity marker. All laboratory analyses will be completed using plasma samples and determined by enzyme-linked immunosorbent assays in the laboratories of the MASH cohort. Dietary and anthropometric data, disease progression and medical history will be collected. The MASH cohort assesses drug use with questionnaires, urine toxicology, and cocaine metabolites. Results: We hypothesize that drug users infected with HIV, who have vitamin D deficiency or insufficiency, will have higher levels of MT, immune-activation, inflammation and deterioration of the gut integrity than drug users infected with HIV with sufficient Vitamin D levels. Conclusions: The MASH cohort participants are well-characterized and followed longitudinally enabling access to the participants and their information. This study will provide information to develop adjunct therapies for the management of HIV, gut health and nutrition. Funding Sources: The National Institute of Drug Abuse provides funding for the MASH cohort.